2012
DOI: 10.1111/j.1475-6773.2012.01465.x
|View full text |Cite
|
Sign up to set email alerts
|

California's Minimum Nurse Staffing Legislation: Results from a Natural Experiment

Abstract: Objective. To determine whether, following implementation of California's minimum nurse staffing legislation, changes in acuity-adjusted nurse staffing and quality of care in California hospitals outpaced similar changes in hospitals in comparison states without such regulations. Data Sources/Study Setting. Study Design. We grouped hospitals into quartiles based on their preregulation staffing levels and used a difference-in-difference approach to compare changes in staffing and in quality of care in Californi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
79
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(82 citation statements)
references
References 23 publications
3
79
0
Order By: Relevance
“…27,28 Given concern that payment reductions may affect staffing levels at hospitals because hospitals cut back on labor inputs in response to financial pressure, 2932 nine nursing-sensitive patient safety and inpatient quality indicators were created. The California legislature passed Assembly Bill 394 (AB394) mandating minimum licensed nurse-to-patient ratios in October 1999, but this law was not implemented until January 2004 3335 and should not influence our findings. These nine indicators were death in low mortality DRGs (PSI02), pressure ulcer (PSI03), selected infections due to medical care (PSI07), postoperative hemorrhage or hematoma rate (PSI09), postoperative pulmonary embolism or deep vein thrombosis rate (PSI12), acute myocardial infarction mortality (IQI15), congestive heart failure mortality (IQI16), acute stroke mortality (IQI17), and pneumonia mortality (IQI20).…”
Section: Methodsmentioning
confidence: 91%
See 1 more Smart Citation
“…27,28 Given concern that payment reductions may affect staffing levels at hospitals because hospitals cut back on labor inputs in response to financial pressure, 2932 nine nursing-sensitive patient safety and inpatient quality indicators were created. The California legislature passed Assembly Bill 394 (AB394) mandating minimum licensed nurse-to-patient ratios in October 1999, but this law was not implemented until January 2004 3335 and should not influence our findings. These nine indicators were death in low mortality DRGs (PSI02), pressure ulcer (PSI03), selected infections due to medical care (PSI07), postoperative hemorrhage or hematoma rate (PSI09), postoperative pulmonary embolism or deep vein thrombosis rate (PSI12), acute myocardial infarction mortality (IQI15), congestive heart failure mortality (IQI16), acute stroke mortality (IQI17), and pneumonia mortality (IQI20).…”
Section: Methodsmentioning
confidence: 91%
“…Thus, they may take actions to sustain quality of care despite DSH reductions. 47 Third, even though California implemented regulations requiring minimum levels of licensed nurse staffing after our study period (e.g., beginning in 2004), 3335 hospitals may have anticipated this new regulation. Therefore, rather than cutting back on labor inputs in response to DSH payment reductions, hospitals may have maintained or increased their nurse staffing and as a result, quality of care was not affected.…”
Section: Discussionmentioning
confidence: 99%
“…One study found a significant decrease in failure to rescue rates in some Californian hospitals (Mark et al, 2012) but the pattern of difference was not clearly linked to staffing increases. The largest (and significant) decreases in failure to rescue were observed in both hospitals with the worst pre legislation staffing (which had the greatest increase in staffing levels) and in hospitals with the highest pre-legislation staffing levels (which had the smallest staffing increase).…”
Section: E F F E C T I V E a P P R O A C H E S F O R I D E N T I F Y mentioning
confidence: 99%
“…At an international level, research on the association between the workload of the nursing team and patient safety outcomes includes in the discussion the number of patients assigned to each nurse or nursing assistant and the conditions of the working environment (1,(3)(4)(8)(9)(10)(11) . In Brazil, there is still a long way to go before subsidizing the implementation of the minimum parameters for adequate staffing, as it is established by nursing official organizations in the country (12) with the objective of balancing the number of patients per nursing professional in health institutions.…”
Section: Introductionmentioning
confidence: 99%